Editorial: the burden of alcohol‐related liver disease emergency admissions in England may be twice as high as previously thought—authorsʼ reply. Issue 4 (29th January 2023) - Bodger, Keith; Dhanda, Ashwin
LINKED CONTENT: This article is linked to Dhanda et al papers. To view these articles, visit https://doi.org/10.1111/apt.17307 and https://doi.org/10.1111/apt.17335